Perancangan Maskot Kampanye PROKES (Program Kembali Ke Sekolah) Untuk Mendukung PTM Terbatas di SMP Bina Taruna Bandung - Olivine Alifaprilina Supriadi; Rahmiati Aulia; Aisyi Syafikarani; Siti Hajar Komariah; Aria Ar Razi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Mascot is a visual identity that can be used to represent an organization, event, or product. Mascot design can be applied in a campaign activity to strengthen the image and identity that is conveyed to the audience. PROKES is a socialization campaign held at SMP Bina Taruna Bandung in order to support limited PTM (Face-to-Face Learning) activities in the school environment. The method used for the design and data collection is interpretative qualitative, with the design process being carried out in stages and in a structured manner. Based on the evaluation of the campaign, both as a whole and in the context of visual identity, the response from the residents of SMP Bina Taruna was considered good and positive. The PROKES campaign mascot is expected to be an identifier that reflects the concept of the activity. Keywords: campaign, mascot, SMP Bina Taruna, visual identity